The burial and exhumation history of the Liuqu Conglomerate in the Yarlung Zangbo suture zone, southern Tibet: Insights from clumped isotope thermometry. (1st May 2019) - Ning, Zijie; Zhang, Laiming; Huntington, Katharine W.; Wang, Chengshan; Dai, Jingen; Han, Zhongpeng; Passey, Benjamin H.; Qian, Xinyu; Zhang, Jiawei
Graphical abstract: Highlights: Clumped isotope paleothermometry is applied to paleosol in the Liuqu Conglomerate. The estimated maximum burial temperature of the Liuqu Conglomerate is ∼97 °C. The maximum burial depth of the Liuqu Conglomerate was up to 3.7–4.3 km. The model of outward growth of the Tibetan Plateau is preferred. Abstract: The Liuqu Conglomerate, exposed along the Yarlung Zangbo suture zone (YZSZ) in southern Tibet, archives not only the process of the India-Asia collision, but also the exhumation history of the India-Asia collision zone. The burial and exhumation history of the Liuqu Conglomerate thus could potentially provide clues to the India-Asia collision and orogeny. Low-temperature thermochronometric data indicate that maximum burial temperatures of the Liuqu Conglomerate ranged from 80 to 110 °C; however, the exact burial history is not well constrained. Here, we examine the burial conditions of the Liuqu Conglomerate by applying clumped isotope thermometry to paleosol carbonates. Extensive microcrystalline recrystallization indicates that the samples have been diagenetically altered during burial. Moreover, the clumped isotope temperatures (ranging from ∼48 to ∼97 °C) are clearly above Earth surface conditions, indicating the original climatic information was overwritten by alteration at higher burial temperatures. Nevertheless, the calculated diagenetic water δ 18 O values represent maximum meteoric water values that can be used to broadly constrain the paleoelevation. The highest clumped isotope temperature implies that the maximum burial temperature of the Liuqu Conglomerate was at least ∼97 °C. We conclude that the Liuqu Conglomerate was buried as deeply as 3.7–4.3 km during the latest Paleocene to Eocene, and then exhumed during the Miocene (∼10–12 Ma). Incision of the paleo-Yarlung River was likely responsible for erosion and exhumation of the Liuqu Conglomerate, which suggests that the drainage system of Paleo-Yarlung River was similar to that of today and supports the model of outward growth of the Tibetan Plateau.